New water mite species of the genus Piona Koch, 1842 (Acari, Hydrachnidia: Pionidae) from Northeastern Russia - Tuzovskij, Petr V. (Zootaxa, 2013)
Descriptions of two new water mite species, Piona magadanensis (male, female, deutonymph), Piona anadyrensis (male, female, deutonymph) and one new subspecies P. interrupta interruptella (female) from standing waters of the Magadan Province and Chukotka of Russia are presented.